Negotiations on a free trade agreement between India and the EU: Ambitions, expectations, obstacles, and incentives - Hanns Günther Hilpert; Bettina Rudloff; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2023)
In summer 2022, the European Union (EU) and India resumed negotiations on a free trade agreement to strengthen their strategic partnership. In addition, both sides are negotiating an investment protection agreement and an agreement on the protection of geographical indications. In this way, the EU wants to diversify its relations with the Indo-Pacific states and underscore India's prominent position. Through cooperation with the EU, India aims to advance its economic and technological modernisation, which is indispensable if the country is to play a greater international role. Unlike the negotiations that failed in 2013, the current negotiations are paradoxically both simpler and more complicated. They are simpler because the EU and India are now more aligned on geopolitical issues than ever, especially with regard to China. But they are also more complicated because the success of the negotiations still depends on difficult concessions on both sides. A repeat failure is not an option, however, for either India or the EU in terms of the future of their strategic partnership.
Keywords: 320; European Union (EU); India; negotiations on a free trade agreement; strategic partnership